Impacts of land use change on soil respiration and elemental carbon in the forests of Karasu district - Oral, Hasan Volkan. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2010., 2010)
In recent years, expansion of agricultural activities in the Karasu region which is located in northwest Turkey has led to significant deforestation. As a result, deforestation in this region is one of the most critical in Turkey. The purpose of this study is to evaluate the impact of land use change on soil respiration, soil elemental carbon in the Karasu District. The study also assess the potential seasonal changes on these three key parameters. To achieve this purpose, field trips were carried out over four seasons in 2008-2009. In total 900 soil samples from forested and deforested lands were collected. Geographical Information Systems (GIS) Remote Sensing Technologies (RST) were employed in conjunction with in situ measurements, laboratory experiments and statistical analyses. Soil respiration was measured in situ while soil samples were collected for the laboratory determination of soil elemental carbon (C) and nitrogen (N), C:N ratio, microbial respiration, soil organic matter (SOM), electrical conductivity, gravimetric moisture content, pH and soil textural structure. Analysis of the collected data indicated that the differences in mean soil respiration and elemental carbon due to land use and seasonal variations were statistically significant. The average annual soil respiration and elemental carbon in forested lands was about 27% and 34% higher than that from deforested lands. The statistical analyses also showed that the clay content exhibited high correlations with soil respiration and, particularly, with elemental carbon. Geostatistical analysis was conducted to calculate the spatial average values of soil respiration, surface elemental carbon. The data analyses and interpretation methods developed in this study can serve as an example for future studies in other geographical regions involving the evaluation of soil carbon content and emissions.
Keywords: Land use.; Soil respiration.; Geographic information systems.